2019
DOI: 10.1371/journal.pone.0212745
|View full text |Cite
|
Sign up to set email alerts
|

Tunnel millisecond-delay controlled blasting based on the delay time calculation method and digital electronic detonators to reduce structure vibration effects

Abstract: The reasonable delay time of millisecond-delay blasting using digital electronic detonators can significantly reduce the vibration effects induced by tunnel blasting. This study proposes a method for calculating the delay time for cut holes, easer holes and periphery holes, considering the rocks breaking effect as well as wave superposition theory. And then according to the actual layout diagram of the tunnel holes, the delay time calculation formulas of different holes are put forward. Then the delay times we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Because the actual and the nominal delay of detonator have large discreteness [37][38][39], there is normally a delay error. Terefore, in the actual initiation process, a hole-by-hole initiation with a small delay time was adopted [40][41][42][43]. Te time settings of hole initiation sequence are shown in Figure 4.…”
Section: Detonation Tubes Detonated Hole-by-holementioning
confidence: 99%
“…Because the actual and the nominal delay of detonator have large discreteness [37][38][39], there is normally a delay error. Terefore, in the actual initiation process, a hole-by-hole initiation with a small delay time was adopted [40][41][42][43]. Te time settings of hole initiation sequence are shown in Figure 4.…”
Section: Detonation Tubes Detonated Hole-by-holementioning
confidence: 99%
“…e particle vibration velocity can be effectively suppressed by controlling the explosive quantity for a single detonation. Moreover, the explosive consumption per cubic meter of rock in tunnel excavation is relatively fixed, and the quantity of a single stage is inversely proportional to the number of sections at a certain unit of explosive consumption [3,11,25]. erefore, the blasting technology using phase-difference vibration mitigation can be achieved via effectively controlling the time difference of single-stage detonation [23,25].…”
Section: Design Principle Of Blasting Vibration Reductionmentioning
confidence: 99%
“…Previous studies have shown that the superposition and attenuation of stress waves for porous blasting are related to both the time difference of detonation and the physical property of the surrounding rock [12]. With the development and application of digital electronic detonator technology [24,25], it is possible to reduce the blasting vibration velocity by the time difference of detonation on the basis of the superposition principle of blasting stress waves. Subject to the complexity of the actual working conditions, the amount of experimental and theoretical research conducted in this area is very limited; especially in a new tunnel excavation adjacent railway tunnel, the construction standard is extremely strict and the specification cannot be unified.…”
Section: Introductionmentioning
confidence: 99%
“…Exploitation of the deposit by means of rock blasting technique has a positive importance in the aspect of ore extraction and in the fight against the threat of tremors arising in the upper floor layers, however, there is the possibility of harmful effects on the stability of the bolted roof in adjacent excavations. First of all, damages to the roof excavation may consist of an increasing number and extent of fractures [25][26][27]. In addition, loose irregular rock blocks may form in the roof space, which may move into the interior of the excavation.…”
Section: The Influence Of Technological Seismic Event On the Bolted Roofmentioning
confidence: 99%